2013
DOI: 10.1590/0004-282x20130139
|View full text |Cite
|
Sign up to set email alerts
|

The blink reflex test does not show abnormalities in a large group of patients with chronic migraine

Abstract: The blink reflex – a simple, non-invasive and inexpensive test – may be indicative of lesions or dysfunctions of the brainstem, and particularly assesses the trigeminal-facial arch. Results from alterations of the blink reflex in patients with headaches have provided controversial data. Method Registration of the waves R1 and R2 (ipsilateral to the stimulus) and R2c (contralateral to the stimulus) by electroneuromyography. Results A large number of controls (n=160) and patients with chronic migraine (n=160)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
(26 reference statements)
0
10
0
1
Order By: Relevance
“…In addition, the possibility that increased excitability of the trigeminal pathways may persist during the interictal period has been proposed in EM [ 15 ]; however, investigations of trigeminal sensory pathways in CM, particularly in regard to nociceptive processing, are rare. One previous study did not observe any changes [ 16 ], whereas other studies observed abnormal excitability [ 13 , 17 ]. These inconsistencies may result from the use of different study techniques, such as the conventional blink reflex, or different study groups, such as in individuals with combined medication-overuse headaches.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the possibility that increased excitability of the trigeminal pathways may persist during the interictal period has been proposed in EM [ 15 ]; however, investigations of trigeminal sensory pathways in CM, particularly in regard to nociceptive processing, are rare. One previous study did not observe any changes [ 16 ], whereas other studies observed abnormal excitability [ 13 , 17 ]. These inconsistencies may result from the use of different study techniques, such as the conventional blink reflex, or different study groups, such as in individuals with combined medication-overuse headaches.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that these findings can be considered evidence that migraine-specific trigeminal dysfunction is a transient condition [21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Th e second response, R2, involves a pathway of descent to the spinal trigeminal tract. Th e contralateral response, R2c, refl ects the crossing of the brainstem in the medulla and progresses through the reticular formation to elicit a response at the contralateral facial nucleus [7][8][9] . Th e results obtained by testing the blink refl ex in patients with headaches have been very heterogeneous.…”
Section: Introductionmentioning
confidence: 99%